Neural Sequential Malware Detection with Parameters - Agrawal, Rakshit; Stokes, Jay; Marinescu, Mady; Selvaraj (RESEARCH), Karthik (2018 International Conference on Acoustics, Speech, and Signal Processing, 2018)
Sequential models which analyze system API calls have shown promise for detecting unknown malware. Athiwaratkun and Stokes recently proposed a two-stage model which uses a long short-term memory (LSTM) model for learning a set of features which are then input to a second classifier. Kolosnjaji et al., first use a convolutional neural network followed by an LSTM to predict unknown malware. However, neither of these models consider the parameters which are input to the system API calls. These input parameters offer significant information regarding malicious intent. In this paper, we extend Athiwaratkun's model to include each system API call's two most input parameters. We then show that the proposed model dominates these previously proposed models in terms of the receiver operating characteristic (ROC) curve.